Tapping the pathogenic bacteria from hospital water tap system in Malaysia using flongle nanopore - Zainulabid, Ummu Afeera; Siew, Shing Wei; Kamarudin, Norhidayah; Periyasamy, Petrick; Ahmad, Hajar Fauzan (Elsevier, 2023)
The hospital water supply is a reservoir of nosocomial infection that is often neglected. Mounting studies showed that disease transmission in hospitals is caused by the pathogenic bacteria in the water system that carry antibiotic resistance genes (ARGs). Hence, this study was conducted as infection surveillance in monitoring disease transmission.